ANALISIS KOMPARATIF PENDAPATAN USAHATANI KAKAO FERMENTASI DAN NON FERMENTASI (STUDI KASUS DI DESA SINTUWU KECAMATAN PALOLO KABUPATEN SIGI) - Hayatudin Hayatudin; Hadayani Hadayani; Rustam Abd Rauf (Universitas Tadulako, 2020)
Comparative analysis between the income of fermentation and non fermentation cocoa farming system was conducted aiming at identifying differences in their production, revenue and income at Sintuwu village of Palolo sub-district of Sigi district. This research location was selected purposively with consideration that it is a cacao producer in Palolo sub-district of Sigi district and its community mostly farmers who generally growing cacao. Respondent samples were selected by a simple random sampling technique. Therespondents were 48 farmers who produced fermented cocoa (26 farmers) and non fermented cocoa (26 farmers). Data was analyzed using production cost analysis, farm revenue analysis and farm income analysis. The production of the fermented cocoa was 13,228 kg/year less than that of the non-fermented cocoa (15,140 kg/year). The average price of the fermented cocoa was IDR 30,000/kg where as that of the non-fermented cocoa was IDR 26,000/kg. The revenue of the fermented cocoa farming system was IDR 398,228,000/year slightly higher than the non fermented cocoa (IDR 393,090,000/year). The income generated from the fermented cocoa farming system was IDR 297.900.878/year larger than that from the non fermented cocoa amounting to IDR 288.171.251/year. Keywords: Comparative, Farming, Income, Production and Revenue.